Forecasting the Southeast Asian Currencies against the British Pound Sterling Using Probability Distributions - Ahmad Abubakar Suleiman; Hanita Daud; Mahmod Othman; Abdullah Husin; Aliyu Ismail Ishaq; Rajalingam Sokkalingam; Mohd. Lazim Abdullah; Iliyas Karim Khan (Data Science Insights, 2023)
The current study aimed to identify the most suitable probability distribution function (pdf) for modeling the exchange rates of three countries. Financial data is essential to many people and to the management of a country. Volatility in financial data influences individual and the country's economic growth. This volatility in the exchange rates between the Malaysian Ringgit (MYR), Singapore Dollar (SGD), and Thailand Thai Baht (THB) against British Pound Sterling (GBP) is found to be very high which make it difficult to model and forecast. This is what has necessitated the development of an accurate and reliable approach for assessing and reducing the risks of trading in any of these currencies.